2013
DOI: 10.5194/esd-4-385-2013
|View full text |Cite
|
Sign up to set email alerts
|

Implications of accounting for land use in simulations of ecosystem carbon cycling in Africa

Abstract: Abstract. Dynamic global vegetation models (DGVMs) are important tools for modelling impacts of global change on ecosystem services. However, most models do not take full account of human land management and land use and land cover changes (LULCCs). We integrated croplands and pasture and their management and natural vegetation recovery and succession following cropland abandonment into the LPJ-GUESS DGVM. The revised model was applied to Africa as a case study to investigate the implications of accounting for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
209
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(211 citation statements)
references
References 73 publications
(100 reference statements)
2
209
0
Order By: Relevance
“…PLUM can reproduce global historic agricultural land use change , and results have demonstrated that agricultural land use is highly sensitive to uncertainties in crop yield growth rates . To estimate the temporal trends and changes in spatial patterns of crop yields in response to climate change, country-level cereal yields were derived from the global dynamic vegetation model LPJ-GUESS (Lindeskog et al, 2013;Smith et al, 2001). LPJ-GUESS accounts for the effects of temperature, precipitation and atmospheric CO 2 concentrations on crop yields and the productivity of natural vegetation.…”
Section: Plum Simulations -Descriptions Of Future Croplandmentioning
confidence: 99%
See 2 more Smart Citations
“…PLUM can reproduce global historic agricultural land use change , and results have demonstrated that agricultural land use is highly sensitive to uncertainties in crop yield growth rates . To estimate the temporal trends and changes in spatial patterns of crop yields in response to climate change, country-level cereal yields were derived from the global dynamic vegetation model LPJ-GUESS (Lindeskog et al, 2013;Smith et al, 2001). LPJ-GUESS accounts for the effects of temperature, precipitation and atmospheric CO 2 concentrations on crop yields and the productivity of natural vegetation.…”
Section: Plum Simulations -Descriptions Of Future Croplandmentioning
confidence: 99%
“…The direction of socio-economic drivers is referred to as deep uncertainties, which are addressed through the use of scenarios (van Vuuren et al, 2008). Cropland projections at the high end of the projected uncertainty range for global cropland would have profound consequences for, for example, global carbon and nitrogen fluxes, the global water balance, biodiversity, and other ecosystem services (Lindeskog et al, 2013;Pereira et al, 2012;Zaehle et al, 2007). Hence, quantifying and understanding the inherent uncertainties in the drivers of LULCC has important consequences for policy responses to support sustainable development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural and pastoral systems are 10 represented as a prescribed fractional cover of area under human land use per grid cell. Four crop functional types modelled on winter wheat, spring wheat, rice, and maize were used to simulate croplands , with representation of sowing, harvesting, irrigation, fertilisation, tillage, and the use of cover crops (Lindeskog et al, 2013;Olin et al, 2015;Pugh et al, 2015). Pastures are represented by competing C3 and C4 grass, with 50% of the above-ground biomass removed annually to 15 represent the effects of grazing (Lindeskog et al, 2013).…”
Section: Case Studymentioning
confidence: 99%
“…Four crop functional types modelled on winter wheat, spring wheat, rice, and maize were used to simulate croplands , with representation of sowing, harvesting, irrigation, fertilisation, tillage, and the use of cover crops (Lindeskog et al, 2013;Olin et al, 2015;Pugh et al, 2015). Pastures are represented by competing C3 and C4 grass, with 50% of the above-ground biomass removed annually to 15 represent the effects of grazing (Lindeskog et al, 2013). A general circulation model (GCM) emulator, IMOGEN, provides feedback between the carbon cycle and climate to be investigated without the computational demands of running a full Earth System Model (Huntingford et al, 2010).…”
Section: Case Studymentioning
confidence: 99%